(untitled) (Global Journal of Science Frontier Research, 2015)
Acid phosphatases (AcPs) are known to provide phosphate to tissues that have high energy requirements, especially during development, growth and maturation. AcPs is a lysosomal enzyme as it is lytic and destructive in nature. In the present investigation the attempt was made to localize this enzyme in the intestine, liver and kidney during the developing stages of Labeo rohita. For the histochemical localization of this enzyme activity, sodium β-glycerophosphate was used as a substrate. The AcPs activities in the developing stages were increased gradually from 24hr hatching to 60mm stage. It was concluded that the presence of AcPsin the yolk sac might be due to its role in the yolk metabolism. Gradual increase in enzyme activity from 10mm onwards in the intestine could be due to maturation of digestive tract and in the liver due to increase in the metabolic load with increase in growth and age.